HUBUNGAN KERJASAMA ANTARA BADAN PENGUSAHAAN BATAM (BP BATAM) DAN PT ADHYA TIRTA BATAM (PT ATB) DALAM PENGELOLAAN AIR BERSIH DI BATAM TAHUN 2019-2020 - Kanaya Medina Yandhria Putri; Muhammad - Adnan; Dewi - Erowati (Journal of Politic and Government Studies, 2023)
This research analyze and explain how the cooperative relationship between the Batam Concession Agency (BP Batam) and PT Adhya Tirta Batam during the concession termination period of 2019-2020. This study also describes and analyzes the prospects for clean water management in Batam City. This study uses a descriptive qualitative approach with in-depth interviews as data collection technique. This research indicate that BP Batam and PT ATB in 2019-2020 carried out their respective duties and obligations until the end of the concession period, but conflicts arose in the process of terminating the concession collaboration, where there were allegations of contract violations and unfair competition in the tender auction process. The prospect of clean water management in Batam City is threatened with a water crisis if detailed and sustainable planning is not carried out.This research concludes that BP Batam and PT ATB had an unfavorable cooperative relationship in 2019-2020 due to conflicts that arose in the concession termination process. Prospects for Batam City’s water management need to be studied further. Plans to cooperate with relevant parties need further attention to the quality of the parties involved so that they are in accordance with the government and the people.